Epidemiology of critically ill children in England and Wales: incidence, mortality, deprivation and ethnicity. Issue 3 (23rd December 2008) - Parslow, R C; Tasker, R C; Draper, E S; Parry, G J; Jones, S; Chater, T; Thiru, K; McKinney, P A; ,
Abstract : Objective: The purpose of this work was to investigate the incidence rate for admission and mortality of children receiving paediatric intensive care in relation to socioeconomic status and ethnicity in England and Wales. Design: National cohort of sequential hospital admissions. Setting: Twenty nine paediatric intensive care units in England and Wales. Participants: All children aged under 16 years admitted to paediatric intensive care in the 4 years 2004–2007. Main outcome measures: Incidence rates for admission and odds ratios (OR) for risk-adjusted mortality by an area based measure of deprivation (Townsend score) and ethnic group (south Asian vs non-south Asian determined using two-name analysis algorithms). Results: The incidence for south Asian children was higher than that of non-south Asian children (138 vs 95/100 000, incidence rate ratio 1.36, 95% CI 1.32 to 1.40). The age-sex standardised incidence for children admitted to paediatric intensive care ranged from 69/100 000 in the least deprived fifth of the population to 124/100 000 in the most deprived fifth. The risk-adjusted OR for mortality for south Asian children was 1.36 (95% CI 1.18 to 1.57) overall, rising to 2.40 (95% CI 1.40 to 4.10) in the least deprived fifth of the population when a statistical interaction term for deprivation was included. Conclusions: In England and Wales, the admission rate to paediatric intensive care is higher for children from more deprived areas and 36% higher for children from the south Asian population. Risk-adjusted mortality increases in south Asian children as deprivation decreases.